Molecular cloning and characterization of three carnitine palmitoyltransferase (cpt) isoforms from mud crab (Scylla paramamosain) and their roles in respond to fasting and ambient salinity stress - Lin, Zhideng; Huang, Chaoyang; Zhuo, Zhengrui; Xie, Jun; Lan, Hongliang; Hu, Bixing; Zhang, Chengkang; Han, Kunhuang; Huang, Weiqing (Frontiers in Marine Science, 2024)
As rate-limiting enzymes of β-oxidation of fatty acids in mitochondria, the carnitine palmitoyltransferase (CPT) played an important role in regulating energy homeostasis of aquatic animals. However, there was very little research on β-oxidation of fatty acids in crustaceans. In the present study, the full-length cDNA sequences of cpt-1a, cpt-1b and cpt-2 were isolated from the hepatopancreas of Scylla paramamosain, and contained 4206, 5303 and 3486 bp respectively. Sequence analysis showed that the CPT-1A, CPT-1B and CPT-2 encoded proteins with 777, 775 and 672 amino acids respectively, and only the CPT-1A possessed a transmembrane region. In addition, both the CPT-1B and CPT-2 contained conservative functional domains like N-terminal domain and acyltransferases choActase 2, while the CPT-1A lacked. The results of phylogenetic tree indicated that the CPT-1A, CPT-1B and CPT-2 of S. paramamosain gathered together with their corresponding orthologues from crustaceans. The tissue distribution exhibited that the cpt-1a was highly expressed in hepatopancreas, followed by muscle, eyestalk and cranial ganglia, and the muscle, eyestalk and heart were main expressed tissues of cpt-1b. Furthermore, the high expression levels of cpt-2 were mainly detected in hepatopancreas, muscle and heart. The transcriptional levels of cpt-1a, cpt-1b and cpt-2 were significantly up-regulated under chronic low salinity stress. Besides, at the acute low salinity stress condition, the expression levels of cpt-1a, cpt-1b and cpt-2 in hepatopancreas were dramatically increased in 14‰ and 4‰ salinity groups at the 6h and 48h, while the transcriptional levels of cpt-1a, cpt-1b and cpt-2 in muscle were signally up-regulated in 14‰ and 4‰ salinity groups at the 12h and 24h, showing an alternate response pattern. Similarly, the present study found that fasting could markedly increase the expression levels of cpt-1a, cpt-1b and cpt-2 in hepatopancreas and muscle, especially cpt-1a in hepatopancreas as well as cpt-1a and cpt-1b in muscle. The results above indicated that the cpt-1a, cpt-1b and cpt-2 played a crucial part in providing energy for coping with fasting and salinity stress. These results would contribute to enhancing the knowledge of cpt phylogenetic evolution and their roles in energy metabolism of crustaceans.